Macrophages and small extracellular vesicle mediated-intracellular communication in the peritoneal microenvironment: Impact on endometriosis development - Wang, Yifan; Dragovic, Rebecca A.; Greaves, Erin; Becker, Christian M.; Southcombe, Jennifer H. (Frontiers in Reproductive Health, 2023)
Endometriosis is an inflammatory disease that is defined as the growth of endometrium-like tissue outside the uterus, commonly on the lining of the pelvic cavity, visceral organs and in the ovaries. It affects around 190 million women of reproductive age worldwide and is associated with chronic pelvic pain and infertility, which greatly impairs health-related life quality. The symptoms of the disease are variable, this combined with a lack of diagnostic biomarkers and necessity of surgical visualisation to confirm disease, the prognosis can take an average timespan of 6–8 years. Accurate non-invasive diagnostic tests and the identification of effective therapeutic targets are essential for disease management. To achieve this, one of the priorities is to define the underlying pathophysiological mechanisms that contribute to endometriosis. Recently, immune dysregulation in the peritoneal cavity has been linked to endometriosis progression. Macrophages account for over 50% of immune cells in the peritoneal fluid and are critical for lesion growth, angiogenesis, innervation and immune regulation. Apart from the secretion of soluble factors like cytokines and chemokines, macrophages can communicate with other cells and prime disease microenvironments, such as the tumour microenvironment, via the secretion of small extracellular vesicles (sEVs). The sEV-mediated intracellular communication pathways between macrophages and other cells within the peritoneal microenvironment in endometriosis remain unclear. Here, we give an overview of peritoneal macrophage (pMΦ) phenotypes in endometriosis and discuss the role of sEVs in the intracellular communication within disease microenvironments and the impact they may have on endometriosis progression.